Influences of Linker and Nucleoside for the Helical Self-Assembly of Perylene Along DNA Templates - Fritz, Yannic; Wagenknecht, Hans-Achim (Frontiers in Chemistry, 2019)
Six different conjugates of perylene with 2’-deoxyuridine and with 2-amino-2’-deoxyadenosine were synthesized and applied for DNA-templated assembly in aqueous buffer solutions. They differ by the linkers ethynylene, phenylene and phenylene-ethynylene between nucleoside and chromophore. The nucleosides were investigated as monomers in CHCl3 and DMSO by optical spectroscopy. The properties of the four phenylene-linked conjugates are similar to that of perylene as reference, because these linkers separate both aromatic parts. The ethynylene linker electronically couples the chromophore with the respective nucleoside and thus red-shifts the absorbance. The DNA-templated assembly properties were elucidated by mixing the templates in aqueous buffer with the perylene-nucleoside conjugates from a DMSO stock solution. Specific binding of the nucleosides was probed by comparing the results with dA20 and T20 as single-stranded DNA templates. Our studies reveal the structural parameters that are important for the DNA-templated assembly of perylenes. (i) Perylene-2’-deoxyuridine conjugates do not form DNA-templated helical assemblies, regardless of the choice of linker. (ii) The ethylene linker is crucial for successful DNA-templated chromophore assemblies of perylene-2-amino-2’-deoxyadenosine conjugates. (iii) In contrast, the phenylene linker inhibits self-assembly along single-stranded DNA templates. In conclusion, the 2-amino-2’-deoxyadenosin in combination with the ethynylene linker provides the best structural feature for specific and helical DNA-templated assembly of perylenes. This result is important for the design of future DNA-based supramolecular architectures with chromophores, in particular DNA-based light-harvesting systems and DNA systems for emitting or sensing circularly polarized luminescence.